A Simple Strategy of Control DC-DC Converter as Power Supply on Household Lights - Turahyo, Turahyo (Universitas Muhammadiyah Yogyakarta, 2021)
Light emitting diode (LED) lamps are lighting lamps that have high efficiency with very low power absorption. This lighting lamp is widely used in households, the working voltage is 110-230 volts AC. Under certain conditions, LED light with the driver can also be turned on using a DC voltage at a voltage of 120-125 volts DC. Storage of electrical energy from solar cells generally uses a 12 volt batteries with a large enough current capacity from 5Ah to 400Ah. If the driver LED light is turned on by a battery or battery with a voltage of 12 volts DC from the solar cell, the driver LED light will not light up. This is because the battery / battery voltage level is not high enough to turn on the drive LED light. An electronic device in the form of a DC-DC converter can be utilized to increase the voltage from 12 volts to a higher voltage. In this paper, a DC to DC converter with a voltage multiplier using the Cockcroft-Walton method is designed to be used to turn on LED light for household lighting. After testing, the output voltage from DC to DC is 125.2 volts and the output current is 0.0465 A with a lamp load of 5 watts, while the input voltage is 3.7 volts and the current is 1.49 A.